Hepatocellular carcinoma: ESMO Clinical Practice Guidelines for diagnosis, treatment and follow-up - Vogel, Arndt; Schirmacher, Peter (Annals of oncology, 2018)
The incidence of hepatocellular carcinoma (HCC) has been rising worldwide over the last 20 years and is expected to increase until 2030 in some countries includ
Gesehen am 26.03.2019